IDNLearn.com: Your go-to resource for finding expert answers. Whether it's a simple query or a complex problem, our experts have the answers you need.
Sagot :
To determine the coordinates of the center and the radius of the circle from the given equation:
[tex]\[ x^2 + y^2 - 4x - 10y + 20 = 0 \][/tex]
we need to put the equation into the standard form of a circle, which is:
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
where [tex]\((h, k)\)[/tex] is the center and [tex]\(r\)[/tex] is the radius.
1. Rearrange the Equation:
We start with the given equation:
[tex]\[ x^2 + y^2 - 4x - 10y + 20 = 0 \][/tex]
2. Complete the Square for [tex]\(x\)[/tex] and [tex]\(y\)[/tex] Terms:
To complete the square for the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms, we separate and rearrange the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms:
[tex]\[ x^2 - 4x + y^2 - 10y = -20 \][/tex]
For [tex]\(x\)[/tex] terms:
The expression [tex]\(x^2 - 4x\)[/tex] can be rewritten by completing the square.
[tex]\[ x^2 - 4x \quad \text{becomes} \quad (x - 2)^2 - 4 \][/tex]
For [tex]\(y\)[/tex] terms:
The expression [tex]\(y^2 - 10y\)[/tex] can be rewritten by completing the square.
[tex]\[ y^2 - 10y \quad \text{becomes} \quad (y - 5)^2 - 25 \][/tex]
3. Rewrite the Equation:
Substitute the completed squares back into the equation:
[tex]\[ (x - 2)^2 - 4 + (y - 5)^2 - 25 = -20 \][/tex]
Combine like terms:
[tex]\[ (x - 2)^2 + (y - 5)^2 - 29 = -20 \][/tex]
Simplify the equation:
[tex]\[ (x - 2)^2 + (y - 5)^2 - 29 = -20 \][/tex]
[tex]\[ (x - 2)^2 + (y - 5)^2 = 9 \][/tex]
4. Identify the Center and Radius:
The equation [tex]\((x - 2)^2 + (y - 5)^2 = 9\)[/tex] matches the standard form [tex]\((x - h)^2 + (y - k)^2 = r^2\)[/tex], where:
- [tex]\(h = 2\)[/tex]
- [tex]\(k = 5\)[/tex]
- [tex]\(r^2 = 9\)[/tex], so [tex]\(r = \sqrt{9} = 3\)[/tex]
Therefore, the coordinates of the center of the circle are [tex]\((2, 5)\)[/tex] and the radius is [tex]\(3\)[/tex] units.
Thus, the correct answer is:
C. center: [tex]\((2, 5)\)[/tex]
radius: 3 units
[tex]\[ x^2 + y^2 - 4x - 10y + 20 = 0 \][/tex]
we need to put the equation into the standard form of a circle, which is:
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
where [tex]\((h, k)\)[/tex] is the center and [tex]\(r\)[/tex] is the radius.
1. Rearrange the Equation:
We start with the given equation:
[tex]\[ x^2 + y^2 - 4x - 10y + 20 = 0 \][/tex]
2. Complete the Square for [tex]\(x\)[/tex] and [tex]\(y\)[/tex] Terms:
To complete the square for the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms, we separate and rearrange the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms:
[tex]\[ x^2 - 4x + y^2 - 10y = -20 \][/tex]
For [tex]\(x\)[/tex] terms:
The expression [tex]\(x^2 - 4x\)[/tex] can be rewritten by completing the square.
[tex]\[ x^2 - 4x \quad \text{becomes} \quad (x - 2)^2 - 4 \][/tex]
For [tex]\(y\)[/tex] terms:
The expression [tex]\(y^2 - 10y\)[/tex] can be rewritten by completing the square.
[tex]\[ y^2 - 10y \quad \text{becomes} \quad (y - 5)^2 - 25 \][/tex]
3. Rewrite the Equation:
Substitute the completed squares back into the equation:
[tex]\[ (x - 2)^2 - 4 + (y - 5)^2 - 25 = -20 \][/tex]
Combine like terms:
[tex]\[ (x - 2)^2 + (y - 5)^2 - 29 = -20 \][/tex]
Simplify the equation:
[tex]\[ (x - 2)^2 + (y - 5)^2 - 29 = -20 \][/tex]
[tex]\[ (x - 2)^2 + (y - 5)^2 = 9 \][/tex]
4. Identify the Center and Radius:
The equation [tex]\((x - 2)^2 + (y - 5)^2 = 9\)[/tex] matches the standard form [tex]\((x - h)^2 + (y - k)^2 = r^2\)[/tex], where:
- [tex]\(h = 2\)[/tex]
- [tex]\(k = 5\)[/tex]
- [tex]\(r^2 = 9\)[/tex], so [tex]\(r = \sqrt{9} = 3\)[/tex]
Therefore, the coordinates of the center of the circle are [tex]\((2, 5)\)[/tex] and the radius is [tex]\(3\)[/tex] units.
Thus, the correct answer is:
C. center: [tex]\((2, 5)\)[/tex]
radius: 3 units
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. For dependable answers, trust IDNLearn.com. Thank you for visiting, and we look forward to helping you again soon.